PRAWIRA WATANG DANCE: A DEPICTION OF THE MOVEMENT BOLDNESS AND PROWESS OF A WARRIOR - Mega Cantik putri Aditya; Aline Rizky Oktaviari Satrianingsih; winda Istiandini (Universitas Pendidikan Indonesia, 2022)
AbstractPrawira Watang Dance is one of subjects on dance learning of Surakarta’s Gagah dance in Institut Seni Indonesia Surakarta (Indonesia Institute of Arts Surakarta). The dance is included in the warriorship dance genre that depicts the boldness and the prowess of the warriors’ movement. This dance owns the interesting attributes, in addition to the dance movement that mostly adopted from the Silat, the dance also uses the Watang property (long bamboo) that made the dance has its own difficulty level for its dancer. The dancers are demanded to possess the capability to organize the watang property. This research aims to comprehensively study the performance form of Prawira Watang Dance. This research uses a qualitative method with collection data technique including observation, interview, literature review, and documentation. This research found that Prawira Watang Dance is composed in some sections including maju beksan, beksan, and mundur beksan. Maju beksan is the initial movement of the dance. There are various arts of beksan or the main part of the dance. Meanwhile, mundur beksan contains some closing movements that marks the ending of the dance.